Strategi Politik Identitas Perempuan dalam Pemilihan Umum Legislatif 2019 (Studi tentang Kemenangan Ade Kartika di Daerah Pemilihan II Kabupaten Majalengka) - Alrdi Samsa (Universitas Muhammadiyah Ponorogo, 2021)
This study describes the identity politics strategy of legislative candidates in the local political constellation. The focus of this study is about the victory of Ade Kartika in the electoral area II with the composition of the Districts of Kertajati, Jatitujuh, Ligung and Jatiwangi. This study aims to find out more closely related to the political strategy of candidates for legislative members by using the issue of gender identity as the main capital in the legislative political constellation in 2019. The concept of identity politics is used as an analytical tool to reveal how the identity politics strategy works in winning candidates. This study used descriptive method with a qualitative approach. Data analysis was performed using interview methods and relevant literature studies. As a result, this research shows that women's political strategy is based on aspects of group identity and gender ties.